Prespa as an ecosystem and a lived place: policy recommendations for the integration of the concept of place in ecosystem management of Prespa Lakes - Avramoski, Oliver (Macedonian Journal of Ecology and Environment, 2013)
In recent decades, scholars from both natural and social sciences have been preoccupied with the development of theoretical models and management tools that integrate the concept of place into the theory and practice of ecosystem management. Previous research suggests that the concepts of place and place-based identity can be used as powerful tools for a multi-scalar contextual analysis of person-environment interactions. The purpose of this exploratory study was to contribute to these endeavors by specifically focusing on the ways whereby ideas and concepts of the biophysical environment relate to the construction of place-based identity at the regional scale by using the Prespa watershed as a case study. This paper presents the results of this study following an iterative process of data gathering and analysis of interview transcripts and other ethnographic materials, such as publications, documents, and news reports and articles. The results show that the identity of Prespanners is related to places of various geographical scales (e.g., the home, a village, a sub-watershed, the whole watershed, and a nation), or (most likely) a mixture of all. Because place locates the perspective from which people assign meaning to their biophysical and the social environment, they may adopt different positions on an environmental issue or focus on different values, depending on the importance of a particular place-based identity. The implication for ecosystem management is that people’s perceptions and evaluations of ecosystems and their services are not based solely on utility criteria, but also depend on meanings arising in everyday experience and interactions with places where the self is constantly negotiated, constructed, and reconstructed. By focusing on the context of meanings ascribed to the biophysical environment the concept of place helps understand and unravel the power relations and ideology shaping these meanings. This study highlights the need of research programs and procedures for ecosystem management planning that account for place-based meanings.